2000
DOI: 10.1021/om990820o
|View full text |Cite
|
Sign up to set email alerts
|

Monophospholyl Analogs of Cobaltocenium, Rhodocenium, and Iridocenium Cations. Molecular Structures of [MCp*(η5-PC4H2tBu2)]+BPh4- (M = Co, Rh)

Abstract: Monophosphametallocenium cations of the cobalt group are easily prepared through metathesis of bis(η 5 -2,5-di-tert-butylphospholyl)lead ( 1) with [MCp*X 2 ] 2 (M ) Co, Rh, Ir). Crystal structure analyses confirm their metallocene structures, and electrochemical studies show that [CoCp*(PC 4 H 2 tBu 2 )] + (2) undergoes reversible reduction to a long-lived product at a potential of -0.74 V (vs SCE).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 19 publications
2
31
0
1
Order By: Relevance
“…Recent additions include Ga, [257] Tl, [258] Hf, [259] Ge, [260] Sn, [260] Pb, [260] Cr, [261] Ir, [262] Nd, [263] and Tm. [264] In addition, several h 5 complexes of Group 1 and 2 metals have been structurally characterized, including Na, [265] K, [265] Cs, [266] Ca, [267] and Ba.…”
Section: Phosphametallocenesmentioning
confidence: 99%
“…Recent additions include Ga, [257] Tl, [258] Hf, [259] Ge, [260] Sn, [260] Pb, [260] Cr, [261] Ir, [262] Nd, [263] and Tm. [264] In addition, several h 5 complexes of Group 1 and 2 metals have been structurally characterized, including Na, [265] K, [265] Cs, [266] Ca, [267] and Ba.…”
Section: Phosphametallocenesmentioning
confidence: 99%
“…[33] Considered globally, the data above might be taken to imply a parallel and quite classical relationship between cyclopentadienyl and phospholyl complexes. However, relatively recent demonstrations that a range [38] of late-transition-metal phosphametallocenes can be built around metals other than iron (M = Ru (16); [39][40][41][42][43][44][45][46][47][48] Co + , Rh + , Ir + (17); [49][50][51] Co (18); [52,53] Ni + (19); [54] Ni (20); [54] Scheme 4) have allowed reactivity studies to be pushed further and two unusual results, obtained with phospharuthenocenes, imply a more complex relationship. In an early paper, [40] we showed that the phospharuthenocene complex 22 shows an activity towards trifluoroacetyl electrophiles that is comparable with the homologous phosphaferrocene 21 (Scheme 5).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The challenge in this area stems from the fact that incoming electrophiles tend to react initially at the phosphorus atom of the phospholide [4][5][6] so that, for soft metals, phosphido-bridged dimers [7] are often obtained in place of the desired h 5 -sandwich complexes. These may be seen even in cases which appear particularly favourable to h 5 -coordination, as exemplified in Equation (1).…”
Section: Introductionmentioning
confidence: 99%
“…PMe 3 reacts with 2 at room temperature to provoke a ring-slip reaction that gives the 18ve complex [NiCp*h Ni. We have recently had some success in using the 2,5-di-tertbutylphospholyl ligand 5 [1] to prepare a variety of unusual diamagnetic phosphametallocenes 6-8 [1,2] and the first stable monophosphacobaltocene 9, [3] and were interested to employ the same ligand in an attempt to generate and understand an example of the still-unknown class of paramagnetic phosphanickelocenes. [9][10][11] A number of previous studies could potentially have given rise to phosphanickelocenes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation